The Influence of Work Discipline, Competence, and Job Satisfaction on The Performance of Retail Employees in Cirebon City - Oktaviani Ramadhani; Edy Hartono (Interdisciplinary Social Studies, 2026)
The development of the retail industry in Cirebon City, which is becoming increasingly competitive, requires companies to improve employee performance. However, there are still issues in the field related to productivity, discipline, and unstable work motivation, making performance management an important concern. This study aims to analyze the influence of work discipline (X1), competence (X2), and job satisfaction (X3) on the performance of retail employees (Y) in Cirebon City. The method used was a quantitative associative approach, with data collected through a Likert scale questionnaire. The population consists of around 120 retail employees, and the sample was set to 100 respondents (simple random sampling). The analysis was conducted using multiple linear regression (SPSS 31). The results showed that work discipline (B=0.507; t=4.972; Sig.<0.001), competence (B=0.410; t=3.418; Sig.<0.001), and job satisfaction (B=0.281; t=3.836; Sig.<0.001) had a positive and significant effect on employee performance. Simultaneously, the three variables had a significant effect (F=85.046; Sig.<0.001) with an Adjusted R Square of 0.718, meaning that 71.8% of the variation in performance could be explained by the model. In conclusion, the improvement of retail employee performance in Cirebon City can be optimized through strengthening work discipline, developing competencies, and increasing job satisfaction in an integrated manner.